GARCH-based versus traditional measures of exchange-rate volatility: evidence from Korean industry trade. (2016) - Bahmani-Oskooee, Mohsen; Baek, Jungho; Hegerty, Scott W.
Because economic theory suggests that the effects of exchange-rate volatility on trade flows are not uniformly negative, it is necessary to test them empirically. This literature has grown in recent years to cover numerous country pairs and individual products, proving that these effects are indeed ambiguous. Yet, this has raised another important issue: properly measuring exchange-rate volatility. Previous research used annual data and standard deviation-based measure of exchange-rate volatility. In this paper, we use quarterly data and a GARCH-based measure of volatility to assess sensitivity of trade flows of 70 industries that trade between the USA and Korea. Comparing our findings in this paper to those of previous research, we discover that, indeed, the results are sensitive to different measures of exchange-rate volatility.